Seroprevalence of Herpes Simplex Virus Infection in HIV Coinfected Individuals in Eastern India with Risk Factor Analysis - Soumyabrata Nag; Soma Sarkar; Debprasad Chattopadhyay; Sanjoy Bhattacharya; Rahul Biswas; Manideepa SenGupta (Advances in Virology)
Herpes simplex virus type 2 (HSV-2) is the cause of most genital herpes while HSV-1 is responsible for orolabial and facial lesions. In immunocompromised individuals, like HIV patients, impaired immunity leads to more frequent symptomatic and asymptomatic HSV infection. Fifty-two blood samples from HIV patients with clinically diagnosed HSV infection were taken as cases, while 45 blood samples each from HIV-infected (HIV control) and noninfected patients without any herpetic lesion (non-HIV control) were taken as control. Serum was tested for IgM and IgG antibodies of both HSV-1 and HSV-2 by ELISA. The seroprevalence was compared among the three groups of study population, considering the demographic and socioeconomic parameters. The HSV-2 IgM was significantly higher (p<0.005) in the HIV patient group (34.6%) than the HIV control (2.2%) and non-HIV control (2.2%) groups, whereas HSV-2 IgG seroprevalence was higher in both HIV patient (61.5%) and HIV control (57.8%) groups than the non-HIV control group (17.8%). The prevalence of HSV-2 was significantly higher in persons with multiple partners and in the reproductive age group. The overall seroprevalence of HSV-1 IgM was too low (<5%), whereas it was too high (about 90%) with HSV-1 IgG in all three study groups.